Lightning occurrence density in Guinea. - Bah, Mamadou Lamine; Gomes, Chandima; Tounkara, Mamadou; Davidov, Ari; Anderson, Jim (2014)
This paper presents the preliminary results of the lightning detection system installed in Guinea, a coastal country in West Africa. This is the first time an automated lightning detection system has been installed in the region. The lightning hotspots and cold spots in the country have been identified and the pattern of lightning occurrence has been compared with the thunderstorm occurrence density data collected by ground based meteorological observations. A comprehensive discussion is made on the applications of information obtained from lightning detection system in Guinea and in the region.